RELATIONSHIP OF COMORBID DISEASE WITH THE INCIDENCE OF STROKE IN THE ELDERLY GROUP - Susanti, Nofi; Maulana, Putri Athika (Fakultas Kesehatan Masyarakat, Universitas Jember, 2023)
Stroke has become a degenerative disease that accounts for 74% of deaths worldwide. According to Riskesdas data for 2018, the prevalence of stroke in Indonesia increases significantly as patients age. Comorbid diseases such as hypertension, diabetes mellitus, heart disease, and other diseases increase the risk of stroke. The location of this research is in the North Sulawesi Province, conducted from April to July 2023. The research uses national-scale surveys with a quantitative approach and cross-sectional studies. The population in this study is 7.850 respondents, and after cleaning the data, we used samples of 5.540 respondents. This research aims to analyze the relationship between comorbid conditions and the occurrence of stroke in the elderly population at North Sulawesi Province. The results show that hypertension, diabetes, and heart disease have a meaningful relationship with stroke incidence,however there is no significant correlation between the incidence of stroke and obesity in the elderly group in the Northern Sulawesi Province. Therefore, it is recommend the elderly to adopt a healthy lifestyle and undergo routine medical examinations to avoid the risk of stroke.